Effect of Adipic Acid Concentration on the Isotactic Polypropylene Flat Sheet Using Methyl Salicylate Prepared by TIPS for CO2/N2 Separation - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman; Alia Aqilah, Ghazali (Penerbit Universiti Sains Malaysia, 2019)
Gas separation technology using membrane can effectively remove CO2 from flue gas as well as offer cost-effective installation. However, water vapour in flue gas causes the membrane to swell. Thus, this study focused on the enhancement of the durability and performance of membrane for CO2 and N2 separation where hydrophobic membranes were proposed with the introduction of adipic acid (AA) during preparation. The gas test was carried out using a pure gas permeation set up. A maximum CO2/N2 selectivity of 1.22 and CO2 permeance of 2388 GPU were obtained. Via scanning electron microscopy (SEM), a decreasing membrane pore size distribution was observed on isotactic polypropylene (iPP) with increasing AA in methyl salicylate (MS) membrane. Fourier transform infrared spectroscopy (FTIR) spectra showed no bonding changes between raw iPP and membrane fabricated via thermally induced phase separation (TIPS) method. The highest value of contact angle of the membranes prepared was 106° without the addition of adipic acid. The hydrophobicity was observed to be escalating with the increase of nucleation agent.